MODEL REFLEKSI GRAHAM GIBBS UNTUK MENGEMBANGKAN RELIGIUSITAS - Maria Laksmi Anantasari (Jurnal Teologi (Journal of Theology), 2012)
Mastering the art of self reflection can help the self-maturing process and exploring out life meaning. It can also lead to profound transformation and personal growth, especially for aspects of religiosity. Gibbs offered a model of reflections which can be used. However, it needed some modification. The purposes of this paper was to modify the process of reflection of Gibbss covered in the model, through the analysis and interdisciplinary thinking. The method used was critical text analysis. Modifications to the Gibbss reflection model was done by changing the flow stage of self-reflection and developing the content in each stage. Gibbss model of reflection becomes more comprehensive and a critical tool for personal transformation in achieving religiosity, as the essence of life.